Experimental Analysis and Modeling Research of the Morphological Structure of the Weft-Knitted Loop (Journal of Fiber Bioengineering and Informatics, 2012)
To address the limitations of the traditional idealized loop model, this study conducted experimentalanalysis and mathematical model for the morphological structure of the weft-knitted loop, and researchon the method for describing the weft loop's structure and parameters. Because the features of the loop'sstructure is consistent with the Non-uniform Rational Basis Spline (NURBS), three degree NURBS curvewas used to establish the model of the weft loop, and the corresponding value points' coordinate can beobtained by the experimental analysis of the effect of the fabric structure from the structure parameters.In addition, based on the features of the different weft-knitted structure, the models of plain and patternstitch have been established. Research shows NURBS curve modeling can be applied to a more complexweft tissue as well as the basic and variation tissue.
Keywords: Weft Loop's Structure; Morphological Structure; Non-uniform Rational Basis Spline; Experimental Analysis; Loop Structure's Modeling